THE CONCEPT OF TEACHER EDUCATION PROGRAM: THEORITICAL AND PRACTICAL - siti safura (Pedagogik : Jurnal Ilmiah Pendidikan dan Pembelajaran Fakultas Tarbiyah Universitas Muhammadiyah Aceh, 2017)
The aim of teacher education program is to produce a competent teacher for the next future. Teacher quality is always named as the most significant efficiency of teacher education program. This paper discusses the concept of teacher education program that influence the performance of teacher. This paper aims to analyze the teacher preparation program and ponder the preparation program in creating novice teacher to be the professional teacher for future. This paper serves the view of the teacher education program and how this program prepares novice teacher in Indonesia. This paper also focuses on whether this program constitutes as a program that enable the student teachers in implementation their tasks in the teaching process for the future. The result of this program is expected to be able to deliver the professional and competent educators.